Polymer-Based Nanocomposite Coating Methods: A Review - Mathai, S.; S. Shaji, P. (Journal of Scientific Research, 2022)
Coating technology is widely recognized as the most cost-effective and efficient method of preventing metal corrosion. Polymers have been regarded as a powerful coating material owing to their excellent barrier qualities, simplicity of modification, and large-scale production. Nanomaterials differ significantly from their physical and chemical properties, and have been hailed as highly promising functional materials in a wide range of applications, affecting nearly every aspect of science and technology. The addition of organic or inorganic nanofiller particles to polymer nanocomposite coatings may improve corrosion protection and lower the possibility of blistering or delamination. High hardness for polymer coatings, on the other hand, could be achieved by forming hard nanocrystalline phases inside the matrix. This article provides an overview of recent developments in polymer nanocomposite coatings in terms of their history, coating methods, properties, features, and drawbacks.